2011
DOI: 10.1103/physrevb.83.075125
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of strained ultrathin films of strongly correlatedLaNiO3

Abstract: An optical study of fully strained ultrathin LaNiO3 films is presented and compared with LDA+DMFT calculations. LaNiO3 films were grown by pulsed laser deposition on LaAlO3 and SrTiO3 substrates which provide compressive and tensile strain, respectively. Optical conductivity data show a Drude peak with a spectral weight that is significantly reduced compared to that obtained from LDA calculations. The extended Drude analysis reveals the presence of a pseudogap around 80 meV for the film on SrTiO3 and near 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 41 publications
7
39
0
Order By: Relevance
“…Ionic movements make polarization slightly smaller and larger under the zero and +3% strain, respectively, with respect to the unrelaxed results (solid red line with open boxes). It is found that the relaxation-induced change becomes much larger in the compressively strained situation, which is attributed to the large ionic displacement along the out-of-plane direction caused by the compressive in-plane strain, and the volume conservation often being observed in the related materials 12,18 . In the zero strain case, the optimized distance between Ni and apical oxygen is ∼ 2.04Å .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Ionic movements make polarization slightly smaller and larger under the zero and +3% strain, respectively, with respect to the unrelaxed results (solid red line with open boxes). It is found that the relaxation-induced change becomes much larger in the compressively strained situation, which is attributed to the large ionic displacement along the out-of-plane direction caused by the compressive in-plane strain, and the volume conservation often being observed in the related materials 12,18 . In the zero strain case, the optimized distance between Ni and apical oxygen is ∼ 2.04Å .…”
Section: Resultsmentioning
confidence: 95%
“…Vacuum layer thickness is of 7.0Å which is large enough to make the basis function overlap negligible. While the polar surface may not be well stabilized in general, these instability can be compensated by the large covalency in the nickelates 11,12,17,18 . The geometry relaxation has been performed with the force criterion of 10 −3 Hartree/Bohr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LaNiO 3 has already been characterized experimentally via ARPES [14][15][16], optical conductivity [17][18][19], and thermodynamic measurements [20][21][22], as well as theoretically with DFT [23][24][25], DFT + DMFT [6,8,[26][27][28][29], and model system [30][31][32] calculations, and a variety of measurements of m /m have previously appeared (to be discussed more later). ARPES offers a particularly direct measure of a material's mass enhancement via momentum-resolved access to the electronic Green's function, which is the fundamental quantity that characterizes electron propagation in a material:…”
Section: Introductionmentioning
confidence: 99%
“…We do find one subtle caveat: the Ni e g states experimentally exhibit dynamical correlation effects, which we are unable to capture in either the LSDA, LSDA+U , or hybrid functionals. This enhanced spectral weight at the Fermi level has recently been reproduced experimentally and through LDA+dynamical meanfield theory (DMFT) calculations, [72][73][74] where a dynamic (frequency-dependent) treatment of the Ni 3d electronelectron interactions leads to an enhanced effective mass and optical conductivity.…”
mentioning
confidence: 99%